BIOINFORMATICS FOR UNDERGRADUATE BIOLOGICAL SCIENCES STUDENTS USING ACTIVE METHODOLOGY: A CASE STUDY (Revista Brasileira de Ensino de Ciências e Matemática, 2025)
With the advancement of Molecular Biology, several datasets have emerged and together with them, there was a need to systematize and analyze these data for the generation of useful information. To perform such a function arises a new area called Bioinformatics, that encompasses the Biological Sciences, Mathematics and Computer Science. Few Brazilian universities offer courses that deal with aspects related to Bioinformatics at the undergraduate level, thus, many biologists leave universities without having any knowledge about Bioinformatics. Because it is an area closely linked to Molecular Biology, Bioinformatics proves to be an important tool to aid in some disciplines teaching, such as Genetics. In this context, the present study aimed to introduce the discipline of Bioinformatics for undergraduate Biological Sciences students, using an active teaching methodology, aiming to evaluate the relevance and importance of this discipline for undergraduates, as well as the effectiveness of this teaching methodology. It was verified that the students themselves feel the need for a more in-depth approach to Bioinformatics in the academic curriculum, besides, it was observed that active methodologies assist in the teaching-learning process of these students, facilitating a meaningful learning.